Differential Assimilation of Inorganic Carbon and Leucine by Prochlorococcus in the Oligotrophic North Pacific Subtropical Gyre - Björkman, Karin M.; Church, Matthew J.; Doggett, Joseph K.; Karl, David M. (Frontiers in Microbiology, 2015)
The light effect on photoheterotrophic processes in Prochlorococcus, and primary and bacterial productivity in the oligotrophic North Pacific Subtropical Gyre was investigated using 14C-bicarbonate and 3H-leucine. Light and dark incubation experiments were conducted in situ throughout the euphotic zone (0–175 m) on nine expeditions to Station ALOHA over a 3-year period. Photosynthetrons were also used to elucidate rate responses in leucine and inorganic carbon assimilation as a function of light intensity. Taxonomic group and cell-specific rates were assessed using flow cytometric sorting. The light:dark assimilation rate ratios of leucine in the top 150 m were ∼7:1 for Prochlorococcus, whereas the light:dark ratios for the non-pigmented bacteria (NPB) were not significant different from 1:1. Prochlorococcus assimilated leucine in the dark at per cell rates similar to the NPB, with a contribution to the total community bacterial production, integrated over the euphotic zone, of approximately 20% in the dark and 60% in the light. Depth-resolved primary productivity and leucine incorporation showed that the ratio of Prochlorococcus leucine:primary production peaked at 100 m then declined steeply below the deep chlorophyll maximum (DCM). The photosynthetron experiments revealed that, for Prochlorococcus at the DCM, the saturating irradiance (Ek) for leucine incorporation was reached at approximately half the light intensity required for light saturation of 14C-bicarbonate assimilation. Additionally, high and low red fluorescing Prochlorococcus populations (HRF and LRF), co-occurring at the DCM, had similar Ek values for their respective substrates, however, maximum assimilation rates, for both leucine and inorganic carbon, were two times greater for HRF cells. Our results show that Prochlorococcus contributes significantly to bacterial production estimates using 3H-leucine, whether or not the incubations are conducted in the dark or light, and this should be considered when making assessments of bacterial production in marine environments where Prochlorococcus is present. Furthermore, Prochlorococcus primary productivity showed rate to light-flux patterns that were different from its light enhanced leucine incorporation. This decoupling from autotrophic growth may indicate a separate light stimulated mechanism for leucine acquisition.